Women, dowries and agency : marriage in fifteenth-century Valencia - Lightfoot, Dana Wessell (Gender in history., 2013)
This text examines labouring-status women in late medieval Valencia as they negotiated the fundamentally defining experience of their lives - marriage. Through the use of notarial records and civil court cases, it argues that the socio-economic and immigrant status of these women greatly enhanced their ability to exercise agency not only in choosing a spouse and gathering dotal assets, but also in controlling this property after they wed.